2019
DOI: 10.5539/ijef.v11n12p136
|View full text |Cite
|
Sign up to set email alerts
|

Retirement Age Farmers’ Exit and Disinvestment from Farming

Abstract: The aging of farmers in the US today coincides with fluctuating incomes resulting from recent market price volatility and policy changes. We evaluate how farmers' retirement or exit, as well as their disinvestment from farming in preparation for retirement, are affected by economic and demographic factors. Exit and disinvestment are modeled as the outcome of intertemporal utility maximization, and farm-level data from the Census of Agriculture are used to estimate the probability of retirement-age farmers' exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In line with other studies (e.g. Griffin et al, 2019), our results revealed that household income and farm size were significantly associated with the perceived higher likelihood of exit to the retirement of ageing farmers. In a similar vein, the study by Hu and Zhong (2013) concluded that farmers' intention to abandon land management has a negative impact on agriculture output.…”
Section: Discussionsupporting
confidence: 93%
“…In line with other studies (e.g. Griffin et al, 2019), our results revealed that household income and farm size were significantly associated with the perceived higher likelihood of exit to the retirement of ageing farmers. In a similar vein, the study by Hu and Zhong (2013) concluded that farmers' intention to abandon land management has a negative impact on agriculture output.…”
Section: Discussionsupporting
confidence: 93%
“…Williamson (2017) shows significant age-related difference in growth trajectories of surviving BFRs between 1999 and 2014. Nadolnyak et al (2019) identified the economic, demographic and weather related factors that affect exit of BFRs, while Griffin et al (2019) evaluated the factors that affect exit of retirement age farmers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, past succession exerted a significant and positive employment growth effect. Griffin, Hartarska, and Nadolnyak (2019) used Census of Agriculture data to estimate the probability of retirement-age farmers' exit and disinvestment for the 1992-2012 period. They found that larger farms were less likely to exit but more likely to disinvest and scale down the operation.…”
Section: Potential Measures Of Farm Business Successmentioning
confidence: 99%